2008
DOI: 10.1002/jbm.b.31091
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of interferon‐loaded magnetic biodegradable microspheres

Abstract: In this work, magnetite (Fe(3)O(4)) nanoparticles with an average size 10 nm modified by sodium oleate were prepared by the modified controlled chemical coprecipitation method, which can be well dispersed in water and linked well with protein molecules because of the presence of -COOH on their surface. Then magnetic poly(lactic acid) (PLA) and poly(lactic-co-glycolic acid) (PLGA) microspheres containing interferon alpha-2b (IFN-a-2b) were prepared by the modified water-in-oil-in-water solvent evaporation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…Magnetic microspheres have been used as targeted delivery systems for interferon alpha-2b, protein drugs, 4′-epidoxorubin, doxorubicin, mitoxantrone, mitomycin C, etoposide, paclitaxel, and oxaliplatin. 22,23 In addition, magnetic delivery systems have been used to deliver radioisotopes. Hafeli et al showed that this delivery method improved tumor cell eradication without any harm to normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic microspheres have been used as targeted delivery systems for interferon alpha-2b, protein drugs, 4′-epidoxorubin, doxorubicin, mitoxantrone, mitomycin C, etoposide, paclitaxel, and oxaliplatin. 22,23 In addition, magnetic delivery systems have been used to deliver radioisotopes. Hafeli et al showed that this delivery method improved tumor cell eradication without any harm to normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Among the method for preparation of PLGA particles, the emulsification-solvent evaporation is the most frequently employed one [19]. The water/oil/water (W/O/W) double emulsion technique has been successfully developed and used to incorporate hydrophilic molecules such as hydrophilic drugs, proteins and nucleotide into the lumen of biodegradable particles [20][21][22][23].…”
mentioning
confidence: 99%
“…clustering (Astete et al 2007) which explains the shifting of the mean particle size and size distribution towards the higher values. The latter explanation may be supported by the study Zhou et al (Zhou et al 2008) who studied the size of interferon loaded found that size of both types of microspheres increased and the size distribution broadened with the increasing amounts of magnetic nanoparticles. On the other hand it is also expected that higher number of Fe 3 O 4 nanoparticles inside the PLGA nanoparticles may adsorb more PLGA, which increases the amount of polymer in a particle, increasing its mass and size.…”
Section: Effect Of Fe 3 O 4 /Plga Weight Ratiomentioning
confidence: 73%